2020
DOI: 10.3390/microorganisms8010133
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Versus Intra-Host Sequence Diversity of pH1N1 and Associated Clinical Outcomes

Abstract: The diversity of RNA viruses dictates their evolution in a particular host, community or environment. Here, we reported within- and between-host pH1N1virus diversity at consensus and sub-consensus levels over a three-year period (2015–2017) and its implications on disease severity. A total of 90 nasal samples positive for the pH1N1 virus were deep-sequenced and analyzed to detect low-frequency variants (LFVs) and haplotypes. Parallel evolution of LFVs was seen in the hemagglutinin (HA) gene across three scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
2
2
0
Order By: Relevance
“…The amino acid substitutions (N44S, V241I, and N369K) in the NA have been reported to facilitate the stability of the virus [ 54 ]. The I188T and N449D mutations in the NA found in this study are similar to those reported in the previous study [ 55 ]; however, the function of the mutations has not been well characterized ( Fig. 5F ).…”
Section: Discussionsupporting
confidence: 90%
“…The amino acid substitutions (N44S, V241I, and N369K) in the NA have been reported to facilitate the stability of the virus [ 54 ]. The I188T and N449D mutations in the NA found in this study are similar to those reported in the previous study [ 55 ]; however, the function of the mutations has not been well characterized ( Fig. 5F ).…”
Section: Discussionsupporting
confidence: 90%
“…The amino acid substitutions (N44S, V241I, and N369K) in the NA have been reported to facilitate the stability of the virus (135). The I188T and N449D mutations in the NA found in this study are similar to those reported in the previous study (136); however, the function of the mutations has not been well characterized. Additionally, the nonsynonymous mutation at E55K, L90I, I123V, E125D, K131E, and N205S in the NS1 involve the inhibition of host gene expressions related to the interferon response (137,138).…”
Section: Discussionsupporting
confidence: 74%
“…(I7) RNA: Orthomyxoviridae influenza Patients with severe symptoms had a higher number of different viral haplotypes. [ 27 ] Diverse groups have higher productivity. (I2) RNA: Orthomyxoviridae influenza Intrahost diversity as a whole and on a specific set of gene segments increased with severity of outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Synergistic interactions at the population level can also influence burst size, viral load and chronicity of infection [ 24 ]. The presence of certain variants in a population, even low-frequency ones, can play a large role in infection severity [ 27 ].…”
Section: Resultsmentioning
confidence: 99%